TINJAUAN YURIDIS TERHADAP TURUT SERTA DALAM TINDAK PIDANA PENGANIAYAAN YANG MENYEBABKAN KEMATIAN (Studi Putusan Nomor : 275/Pid.B/2021/PN.Jkt.Pst) - Fendi Maruba Parlindungan Hutahaean (Law and Communication Journal, 2025)
The purpose of this study is to find out a crime that is sometimes not committed by one person alone but can also involve several people to participate so that the plan to do evil is realized, whether the person acts as the person who does it (pleger), the person who orders it to be done (doenpleger), the person who participates in it (medepleger), or the person who helps to do it (medeplichtige). The research method used in this study is the normative research method. Based on the temporary conclusion, it is known that the form of sentencing for the Criminal Act of Assault with participation in positive law is threatened with a maximum imprisonment of seven years in accordance with Article 351 paragraph (3) of the Criminal Code in conjunction with Article 55 paragraph (1) 1 of the Criminal Code and the author assesses that the application in the case of the Central District Court Decision Number: 275 / Pid.B / 2021 / PN.Jkt.Pst is not yet appropriate and the judge's considerations are not yet optimal or ideal because they are not thorough. In this case, the judge should consider the severity of the assault case in court so that the deterrent effect on the perpetrator is in accordance with what he has done.